PENGARUH KEPEMIMPINAN YANG MEMBERDAYAKAN, KERJASAMA TIM, DAN DUKUNGAN MANAJEMEN TERHADAP MOTIVASI PEGAWAI PADA KPP PRATAMA SURABAYA KARANGPILANG - Raharja, Cahyana Tri; Purwanto, Purwanto; Rahayu, Sri (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the effect of empowering leadership, teamwork, and management support on employee motivation at the KPP Karangpilang Surabaya. The research employed a quantitative approach with a causal associative design. The population consisted of all 86 employees of the KPP Karangpilang Surabaya, and a census method was applied. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS software. The results indicate that empowering leadership, teamwork, and management support each have a positive and significant effect on employee motivation. Simultaneously, the three independent variables significantly influence employee motivation, with a high coefficient of determination indicating strong explanatory power of the model. These findings suggest that employee motivation in public sector organizations is shaped by an integrated combination of leadership practices, team collaboration, and consistent managerial support. This study provides practical implications for public sector managers, particularly in tax administration institutions, to develop integrated human resource management strategies in order to enhance employee motivation and improve public service quality